Preparation process of low-temperature fluid curing agent and stabilized soil building material prepared from low-temperature fluid curing agent

By modifying betaine powder to form a composite network structure, combined with water-based epoxy resin and silane coupling agent, the problems of freezing and insufficient fluidity of low-temperature curing agents in low-temperature environments are solved, achieving the stability and smoothness of the cured soil, making it suitable for low-temperature construction.

CN121248243AActive Publication Date: 2026-01-02UNIV OF JINAN

Patent Information

Application Number
CN202511817274.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-04
Publication Date
2026-01-02
Estimated Expiration
2045-12-04

AI Technical Summary

Technical Problem

Existing low-temperature curing agents are prone to freezing in low-temperature environments, making it difficult to balance fluidity and strength. Furthermore, the use of traditional admixtures can easily lead to abnormal solidification and strength reduction, making it difficult to meet the stability and smoothness requirements of low-temperature construction.

Method used

Modified betaine powder (GB/CMSS-g-MA) is used to form an electrostatic attraction-hydrogen bond-covalent bond composite network structure, which encapsulates and locks in the mixing water. Combined with waterborne epoxy resin emulsion and silane coupling agent, it improves particle dispersion and interfacial bonding, forming a stable solidified soil structure.

Benefits of technology

It effectively prevents freezing at low temperatures, maintains the structural stability of solidified soil, improves fluidity and strength, and ensures the smooth progress of low-temperature construction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121248243A_ABST
    Figure CN121248243A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of building material preparation, and particularly discloses a preparation process of a low-temperature fluid curing agent and a stabilized soil building material thereof, and the preparation process comprises the following steps: (1) adding modified starch into water, uniformly stirring, and removing oxygen; then adding maleic anhydride and persulfate, and heating to react; and after the reaction is finished, adding ethanol, separating out the precipitate, and drying to obtain the CMSS-g-MA. (2) adding glycine betaine into water, uniformly stirring, then adding CMSS-g-MA, and heating to react; and carrying out spray drying on the obtained reaction liquid to obtain the modified betaine powder. And (3) taking sulphoaluminate cement, ordinary Portland cement, a polycarboxylate superplasticizer, a silane coupling agent, the modified betaine powder, hydroxyethyl cellulose and the like as raw materials, and uniformly mixing the raw materials to obtain the low-temperature fluid curing agent. The solidified soil slurry can be better prevented from being frozen in a low-temperature environment, the stability of the internal structure of the solidified soil is kept, and a guarantee is provided for low-temperature construction.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of building material preparation, and in particular to a preparation process of a low-temperature flow-state curing agent and a cured soil building material. BACKGROUND

[0002] The information disclosed in this Background section is only for the purpose of increasing an understanding of the general background of the application and does not necessarily constitute an admission or a recognition that the information forms part of the prior art already known to a person of ordinary skill in the art.

[0003] Ordinary curing agents have a ratio contradiction between flowability and water requirement: when the mixing water content is insufficient, the particles are easily aggregated and lubricated, which leads to substandard flowability and makes it difficult to meet the self-leveling construction requirements; if the mixing water content is increased to improve flowability, it will cause segregation and bleeding, and also lead to further exacerbation of the risk of freezing in low-temperature environments. Ordinary Portland cement-based curing agents have slow hydration reaction and slow strength growth below 5℃, and the internal freezing is easy to occur when the water content is high, which directly damages the integrity of the curing structure.

[0004] Most of the existing low-temperature curing agents are mainly high-activity cementitious materials, such as high-grade cement + active slag, which have a large hydration water requirement, resulting in a further compressed optimization range of flowability and making it difficult to adapt to the needs of various high-flow construction scenarios. The traditional “anti-freezing component + early strength component” compounding scheme also has shortcomings: the anti-freezing component (such as sodium chloride) is easy to cause flocculation reaction with the water reducing agent, which reduces the dispersion effect of the anti-freezing component. The addition of the early strength component (such as sodium sulfate) also damages the flowability of the slurry to varying degrees. In addition, the dosage of such additives needs to be accurately controlled, otherwise it will easily lead to abnormal setting and late strength reduction, and its application is difficult. SUMMARY

[0005] The present application provides a preparation process of a low-temperature flow-state curing agent and a cured soil building material, which can better avoid the freezing of the cured soil slurry in a low-temperature environment and maintain the stability of the internal structure of the cured soil, thereby providing protection for low-temperature construction. Specifically, the technical scheme of the present application is as follows.

[0006] Firstly, the present application provides a preparation process of a low-temperature flow-state curing agent, which comprises the following steps: (1) starch is added to hot water and stirred to gelatinize, then alkali solution and 2-bromo sodium acetate are added and heated to react. After completion, the reaction system is adjusted to neutral, then ethanol is added for precipitation, the precipitate is separated and ground to obtain modified starch.

[0007] (2) Add the modified starch into water, stir until uniform, and then remove oxygen. Then add maleic anhydride (MA) and persulfate for heating reaction. After completion, add ethanol for precipitation, grind the precipitate after separation, and obtain CMSS-g-MA powder.

[0008] (3) Add glycine betaine (GB) into water, stir until uniform, and then add the CMSS-g-MA powder for heating reaction. After completion, spray dry the obtained reaction solution to obtain modified betaine powder (GB / CMSS-g-MA).

[0009] (4) Take sulphoaluminate cement, ordinary portland cement, polycarboxylate superplasticizer, water-based epoxy resin emulsion, silane coupling agent, the modified betaine powder, and hydroxyethyl cellulose as raw materials, mix them uniformly to obtain the low-temperature flowable curing agent.

[0010] Further, in step (1), the mass ratio of the starch to hot water is 1:5-5.8. Optionally, the temperature of the hot water is 80-85℃. By gelatinizing the starch, the active hydroxyl group (-OH) is exposed, and the reaction uniformity is improved.

[0011] Further, in step (1), the mass ratio of the 2-bromo sodium acetate, starch, and lye is 0.5-0.6:2-2.4:0.4-0.44. Optionally, the mass fraction of the lye is 10-12%.

[0012] Further, in step (1), the lye includes at least one of sodium hydroxide, potassium hydroxide, ammonia, lithium hydroxide, etc.

[0013] Further, in step (1), the temperature of the heating reaction is 60-65℃, and the time is 1-2h. The active hydroxyl group reacts with the -COO - provided by the 2-bromo sodium acetate under alkaline conditions, thereby introducing the carboxymethyl group -O-CH2-COONa on the starch to form the modified starch.

[0014] Further, in step (1), at least one of dilute hydrochloric acid and dilute HBr is used to adjust the reaction system to neutral to prevent the hydrolysis of the carboxymethyl group.

[0015] Further, in step (1), the mass ratio of the reaction system to ethanol is 1:1.5-2.

[0016] Further, in step (1), the fineness of the modified starch is 75-100 mesh.

[0017] Further, in step (2), the mass ratio of the modified starch to water is 1:8-9.

[0018] Further, in step (2), the mass ratio of the modified starch, maleic anhydride (MA) and persulfate is 10-12:1.8-2.2:0.1-0.2. Optionally, the persulfate includes at least one of ammonium persulfate, potassium persulfate and the like.

[0019] Further, in step (2), the heating reaction is performed at a temperature of 60-65°C for 1-2h. The persulfate is decomposed to form sulfate free radicals ∙OSO3 - under the heating condition, which can abstract the α-H of the hydroxyl group on the modified starch (CMS) to form an activated site -CH∙-OH. The C=C of the maleic anhydride (MA) is combined with the activated site to form a stable CMSS-g-MA.

[0020] Further, in step (2), the fineness of the CMSS-g-MA powder is 75-100 mesh.

[0021] Further, in step (3), the mass ratio of the glycine betaine, water and CMSS-g-MA powder is 1:6:2-3.

[0022] Further, in step (3), the heating reaction is performed at a temperature of 60-65°C for 1-2h. The -N + of the glycine betaine is combined with the carboxyl group -COO - provided by the carboxymethyl group -O-CH2-COONa in the CMSS-g-MA through the coulomb force, and simultaneously, -COO - is associated with -OH on the modified starch through the hydrogen bond, and the residual C=C in the maleic anhydride (MA) is reacted with -NH2 of the glycine betaine to form a C-N covalent bond. The modified betaine powder (GB / CMSS-g-MA) with the composite network structure is formed through the electrostatic attraction-hydrogen bond-covalent bond mode. Further, in step (4), the proportion of each component in the raw material is: 3-4 parts by weight of sulphoaluminate cement, 3-5 parts by weight of ordinary portland cement, 0.05-0.06 parts by weight of polycarboxylate superplasticizer, 0.4-0.5 parts by weight of water-based epoxy resin emulsion, 0.07-0.1 parts by weight of silane coupling agent, 0.5-0.7 parts by weight of modified betaine powder, and 0.01-0.025 parts by weight of hydroxyethyl cellulose.

[0023] Further, in step (4), the silane coupling agent includes at least one of KH-550, KH-560, KH-570 and the like.

[0024] Further, in step (4), the solid content of the water-based epoxy resin emulsion is 40-43 wt.%.

[0025] Secondly, the application provides a solidified soil building material, comprising the following components: 70-78 parts by weight of soil material, 12-15 parts by weight of the low-temperature fluidized curing agent, and 27-33 parts by weight of mixing water.

[0026] Compared with the prior art, the technical scheme of the application has at least the following beneficial effects: (1) The modified betaine powder (GB / CMSS-g-MA) in the curing agent of the application is a complex network structure formed by electrostatic attraction-hydrogen bond-covalent bond, which can efficiently wrap and lock mixing water, avoid water aggregation and migration in the solidified soil, effectively reduce the free water content that can freeze at low temperature, effectively reduce the freezing point of mixing water in the fluidized solidified soil, and thus better prevent the fluidized solidified soil from freezing at low temperature, facilitate the internal structure to better maintain stability, and provide protection for low-temperature construction.

[0027] (2) The modified betaine prepared by the application is a zwitterionic-polymer composite system, and the intramolecular electric balance can avoid electrostatic combination with the polycarboxylate superplasticizer in the curing agent, and avoid the problems of solidified soil particle agglomeration, slurry fluidity not meeting the standard or segregation and bleeding due to the failure of the polycarboxylate superplasticizer. This is because the modified betaine prepared by the application contains approximately equal amounts of positive groups (-N + (CH3)3) and negative groups (-COO - ) in the molecule, and the two form a stable electric balance through intramolecular Coulomb force, so that the whole molecule is in a state of no net charge, and does not electrostatically attract and combine with the polycarboxylate superplasticizer (the main chain contains a large number of negative carboxyl / sulfonic acid groups). Not only does it avoid the loss of dispersion function of the superplasticizer due to electrostatic neutralization, but also can achieve the effect of adsorption layer superposition through the cooperation of the modified betaine and the polycarboxylate superplasticizer, and enhance the dispersion of the solidified soil particles. This is because: the polycarboxylate superplasticizer is first adsorbed on the surface of the solidified soil particles, and forms a thin barrier through its negative main chain fixation and long side chain to prevent solidified soil particle agglomeration. The modified betaine is supplemented at the vacancies on the particle surface that are not covered by the superplasticizer, and uses a three-dimensional network to support the thin barrier formed by the polycarboxylate superplasticizer into a thick and stable protective layer, and can also increase the negative charge on the particle surface and make the repulsive force between particles stronger. This superposition effect makes the solidified soil particles more uniformly dispersed, and even in the case of low mixing water content, it can still maintain self-leveling. At the same time, the water-based epoxy resin emulsion in the curing agent of the application can form a uniform lubricating film on the surface of the soil material and the cementitious particles, significantly reducing the friction between the particles, so that even in the case of low mixing water content, the solidified soil can still maintain smooth sliding.

[0028] (3) The modified betaine prepared by the application can use its -N + (CH3)3 to be adsorbed on the surface of the sulfoaluminate cement particles, and polarize the Ca2+ , Al 3+ , reduce the ion and mineral lattice binding energy, accelerate the cement hydration, make the required ion for reaction quickly reach the threshold, avoid the problem of slow reaction caused by low temperature leading to solubility reduction. At the same time, the silane coupling agent in the solidifying agent hydrolyzes to generate silicon hydroxyl-SiOH under the alkaline environment provided by the OH - The silicon hydroxyl-SiOH generated by the hydrolysis of the silane coupling agent in the solidifying agent under the alkaline environment provided by the OH BRIEF DESCRIPTION OF DRAWINGS

[0029] The accompanying drawings, which form a part of the specification, are included to provide a further understanding of the application and are incorporated herein in conjunction with the description of the application. The drawings are not to be construed as a limitation of the application.

[0030] Figure 1 is the GB / CMSS-g-MA powder sample graph of the following example 1.

[0031] Figure 2 is the 12h hydration product XRD test graph of the solidified soil building material of the following example 1.

[0032] Figure 3 is the 28d compressive strength test graph of the following example 1.

[0033] Figure 4 is the GB / CMSS-g-MA powder sample graph of the following example 2.

[0034] Figure 5 is the 12h hydration product XRD test graph of the solidified soil building material of the following example 2.

[0035] Figure 6 is the 28d compressive strength test graph of the following example 2.

[0036] Figure 7 is the GB / CMSS-g-MA powder sample graph of the following example 3.

[0037] Figure 8 is the 12h hydration product XRD test graph of the solidified soil building material of the following example 3.

[0038] Figure 9 is the 28d compressive strength test graph of the following example 3.

[0039] Figure 10XRD test pattern of 12h hydration product of cured soil construction material for Example 4 below.

[0040] Figure 11 Compressive strength test pattern of 28d for Example 4 below.

[0041] Figure 12 GB / CMSS-g-MA powder sample pattern for Example 5 below.

[0042] Figure 13 XRD test pattern of 12h hydration product of cured soil construction material for Example 5 below.

[0043] Figure 14 Compressive strength test pattern of 28d for Example 5 below.

[0044] Figure 15 GB / CMSS-g powder sample pattern for Example 6 below.

[0045] Figure 16 XRD test pattern of 12h hydration product of cured soil construction material for Example 6 below.

[0046] Figure 17 Compressive strength test pattern of 28d for Example 6 below.

[0047] Figure 18 XRD test pattern of 12h hydration product of cured soil construction material for Example 7 below.

[0048] Figure 19 Compressive strength test pattern of 28d for Example 7 below. DETAILED DESCRIPTION

[0049] The application will be further described with reference to the following examples. It should be appreciated that these examples are intended to be illustrative only and are not intended to limit the scope of the present application. Unless otherwise indicated, the experimental procedures in the following examples were carried out in accordance with conventional procedures or as recommended by the manufacturer.

[0050] Unless otherwise defined, all technical and scientific terms used in the application have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. The reagents or materials used in the present application can be purchased by conventional means, and unless otherwise specified, the reagents or materials used in the present application are used in accordance with conventional means or as recommended by the manufacturer.

[0051] Furthermore, any method and material similar or equivalent to those described herein can be used in the present application. The technical solutions of the present application will be further described with reference to the accompanying drawings and specific examples.

[0052] Embodiment 1: A preparation process of a solidified soil building material, comprising the following steps: (1) The starch is mixed with hot water at 80℃ at a mass ratio of 1:5, and then stirred and gelatinized. Then, lye (10% sodium hydroxide solution by mass) and 2-bromo sodium acetate are added, and the mixture is heated to 60℃ and reacted for 1.5 hours. The mass ratio of the 2-bromo sodium acetate, starch, and lye is 0.52:2.2:0.43. After completion, the reaction system is adjusted to neutral with dilute hydrochloric acid, and then anhydrous ethanol is added for precipitation. The mass ratio of the reaction system and anhydrous ethanol is 1:1.7. After completion, the precipitate is filtered, ground, and then sieved through a 100-mesh sieve to obtain modified starch.

[0053] (2) The modified starch is mixed with water at a mass ratio of 1:8, stirred uniformly, and then deoxygenated by passing N2. Then, maleic anhydride and ammonium persulfate are added, and the mixture is heated to 60℃ and reacted for 2 hours. The mass ratio of the modified starch, maleic anhydride, and ammonium persulfate is 10:2:0.15. After completion, the obtained reaction system is precipitated with anhydrous ethanol whose mass is twice that of the reaction system, and then the precipitate is filtered, ground, and sieved through a 100-mesh sieve to obtain CMSS-g-MA powder.

[0054] (3) Glycine betaine is mixed with water, stirred uniformly, and then the CMSS-g-MA powder is added, and the mixture is heated to 60℃ and reacted for 2 hours. The mass ratio of the glycine betaine, water, and CMSS-g-MA powder is 1:6:2.5. After completion, the obtained reaction liquid is spray-dried to obtain GB / CMSS-g-MA powder, as shown in Figure 1 .

[0055] (4) The following components are taken in the following proportions: sulphoaluminate cement 3.2 parts by weight, 42.5 ordinary portland cement 4 parts by weight, polycarboxylic acid water reducer 0.05 parts by weight, water-based epoxy resin emulsion with a solid content of 40wt.% 0.45 parts by weight, silane coupling agent (KH-550) 0.08 parts by weight, GB / CMSS-g-MA powder of the present embodiment 0.6 parts by weight, and hydroxyethyl cellulose 0.02 parts by weight. The above components are mixed uniformly to obtain a low-temperature fluidized solidifying agent.

[0056] (5) The following components are taken in the following proportions: soil material 73 parts by weight, low-temperature fluidized solidifying agent of the present embodiment 14 parts by weight, and mixing water 30 parts by weight. The above raw materials are mixed uniformly to obtain a solidified soil building material.

[0057] Performance test: the performance index test results of the cured soil building material prepared in this embodiment are shown in the following table. At the same time, the fluidity is tested according to the Standard Test Method for Controlled Low-Strength Material (CLSM) Slump (ASTM D6103), the setting time (initial setting / final setting) is tested according to the Standard Test Methods for Water Content, Soundness, and Setting of Hydraulic Cement Mortar (GB / T 1346-2024), and the 12h hydration product XRD is tested by using a D8 Advance X-ray diffractometer (the results are shown in Figure 2 , and the compressive strength is tested according to the Standard Test Method for Compressive Strength of Hydraulic Cement Mortars (ASTM C 109) (as shown in Figure 3 ). The compressive strength test specimen is obtained after being cured at 0℃ for 3d, demolded, transferred to a curing box for standard curing for 28d. It can be seen from the XRD test results that the cured soil building material of this embodiment still maintains good hydration degree after low-temperature curing, and the hydration is sufficient, indicating that the anti-freezing performance is good:

[0058] Embodiment 2: a preparation process of a cured soil building material, comprising the following steps: (1) starch is mixed with hot water at 80℃ at a mass ratio of 1:5.5, then stirred and gelatinized, then alkali solution (10% mass fraction of sodium hydroxide solution) and 2-bromoacetic acid sodium are added, and heated to 65℃ for 1 hour, the mass ratio of 2-bromoacetic acid sodium, starch, alkali solution is 0.5:2:0.4. After completion, the reaction system is adjusted to neutral by using dilute hydrochloric acid, then anhydrous ethanol is added for precipitation, the mass ratio of the reaction system and anhydrous ethanol is 1:1.5. After completion, the precipitate is filtered, ground, then passed through an 80-mesh sieve, and modified starch is obtained.

[0059] (2) the modified starch is mixed with water at a mass ratio of 1:9, stirred uniformly, then deoxygenated by introducing N2. Then maleic anhydride and ammonium persulfate are added, heated to 65℃ for 1 hour, the mass ratio of modified starch, maleic anhydride, ammonium persulfate is 11:1.8:0.1. After completion, the obtained reaction system is precipitated by adding anhydrous ethanol with twice the mass of the reaction system, then the precipitate is filtered, ground, and passed through an 80-mesh sieve to obtain CMSS-g-MA powder.

[0060] (3) glycine betaine is mixed with water, then stirred uniformly, then the CMSS-g-MA powder is added, heated to 65℃ for 1 hour, the mass ratio of glycine betaine, water, CMSS-g-MA powder is 1:6:2. After completion, the obtained reaction liquid is spray dried to obtain GB / CMSS-g-MA powder, as shown in Figure 4 .

[0061] (4) Take the following proportions of components: 3 parts by weight of sulphoaluminate cement, 3 parts by weight of 42.5 ordinary Portland cement, 0.05 parts by weight of polycarboxylic acid water reducer, 0.4 parts by weight of water-based epoxy resin emulsion with a solid content of 43 wt.%, 0.07 parts by weight of silane coupling agent (KH-560), 0.5 parts by weight of the GB / CMSS-g-MA powder of the present embodiment, and 0.01 parts by weight of hydroxyethyl cellulose. Mix the above components uniformly to obtain a low-temperature fluid curing agent.

[0062] (5) Take the following proportions of components: 78 parts by weight of soil, 15 parts by weight of the low-temperature fluid curing agent of the present embodiment, and 32 parts by weight of mixing water. Mix the above raw materials uniformly to obtain a cured soil building material.

[0063] Performance test: The performance indicators of the cured soil building material prepared in the present embodiment were tested in the same manner as in Embodiment 1, wherein the XRD test results of the 12h hydration product are shown in Figure 5 , the compressive strength test results are shown in Figure 6 , and the results are shown in the following table. Meanwhile, from the XRD test results, it can be seen that the cured soil building material of the present embodiment still maintains good hydration degree after low-temperature curing, and the hydration is relatively sufficient, indicating that it has good frost resistance:

[0064] Embodiment 3: A preparation process of a cured soil building material, comprising the following steps: (1) Mix starch with hot water at 85℃ at a mass ratio of 1:5.8, then stir and gelatinize, then add alkali solution (12% mass fraction of potassium hydroxide solution), 2-bromo sodium acetate, and heat to 60℃ for 2 hours, the mass ratio of 2-bromo sodium acetate, starch, and alkali solution is 0.6:2.4:0.44. After completion, adjust the reaction system to neutral with dilute hydrochloric acid, then add anhydrous ethanol for precipitation, the mass ratio of the reaction system and anhydrous ethanol is 1:2. After completion, filter out the precipitate and grind, then pass through a 75 mesh sieve to obtain modified starch.

[0065] (2) Mix the modified starch with water at a mass ratio of 1:8.5, stir uniformly, then deoxygenate by passing N2. Then add maleic anhydride and potassium persulfate and heat to 60℃ for 2 hours, the mass ratio of modified starch, maleic anhydride, and potassium persulfate is 12:2.2:0.2. After completion, add anhydrous ethanol with twice the mass of the obtained reaction system for precipitation, then filter out the precipitate and grind, pass through a 75 mesh sieve to obtain CMSS-g-MA powder.

[0066] (3) Glycine betaine and water were mixed and stirred until uniform, then the CMSS-g-MA powder was added and heated to 60°C for 1.5 hours, the mass ratio of the glycine betaine, water, and CMSS-g-MA powder being 1:6:3. After completion, the reaction solution was spray dried to obtain the GB / CMSS-g-MA powder, as shown in Figure 7 .

[0067] (4) The following components were taken in the following proportions: sulphoaluminate cement 4 parts by weight, 42.5 ordinary Portland cement 5 parts by weight, polycarboxylate superplasticizer 0.06 parts by weight, water-based epoxy resin emulsion with a solid content of 40 wt.% 0.5 parts by weight, silane coupling agent (KH-570) 0.1 parts by weight, GB / CMSS-g-MA powder of the present embodiment 0.7 parts by weight, hydroxyethyl cellulose 0.025 parts by weight. The above components were mixed until uniform to obtain a low-temperature flowable curing agent.

[0068] (5) The following components were taken in the following proportions: soil 70 parts by weight, low-temperature flowable curing agent of the present embodiment 12 parts by weight, mixing water 28 parts by weight. The above raw materials were mixed until uniform to obtain a cured-soil building material.

[0069] Performance testing: the various performance indicators of the cured-soil building material prepared in the present embodiment were tested in the same manner as in the above Example 1, wherein the 12h hydration product XRD test results are shown in Figure 8 , the compressive strength test results are shown in Figure 9 , and the results are shown in the following table. At the same time, from the XRD test results, it can be seen that the cured-soil building material of the present embodiment still maintains good hydration degree after low-temperature curing, and the hydration is relatively sufficient, indicating that it has good frost resistance:

[0070] Example 4: A preparation process of a cured-soil building material, comprising the following steps: (1) The following components were taken in the following proportions: sulphoaluminate cement 3.2 parts by weight, 42.5 ordinary Portland cement 4 parts by weight, polycarboxylate superplasticizer 0.05 parts by weight, water-based epoxy resin emulsion with a solid content of 40 wt.% 0.45 parts by weight, silane coupling agent (KH-550) 0.08 parts by weight, glycine betaine powder 0.6 parts by weight, hydroxyethyl cellulose 0.02 parts by weight. The above components were mixed until uniform to obtain a low-temperature flowable curing agent.

[0071] (2) The following components were taken in the following proportions: soil 73 parts by weight, low-temperature flowable curing agent of the present embodiment 14 parts by weight, mixing water 30 parts by weight. The above raw materials were mixed until uniform to obtain a cured-soil building material.

[0072] Performance test: the same as the above-mentioned embodiment 1, the performance index of the cured soil building material prepared in this embodiment is tested, wherein: the 12h hydration product XRD test result is as shown in Figure 10 The compressive strength test is as shown in Figure 11 The results are shown in the following table. At the same time, from the XRD test results, it can be seen that the cured soil building material of this embodiment has almost no hydration reaction after low temperature curing, and the hydration degree is very low, which indicates that its anti-freezing performance is poor:

[0073] Embodiment 5: a preparation process of a cured soil building material, comprising the following steps: (1) starch and water are mixed in a mass ratio of 1:8.5, stirred uniformly, and then deoxygenated by introducing N2. Then maleic anhydride and potassium persulfate are added and heated to 60℃ for 2 hours, and the mass ratio of the modified starch, maleic anhydride and potassium persulfate is 12:2.2:0.2. After completion, the obtained reaction system is precipitated by adding anhydrous ethanol with twice the mass of the reaction system, then the precipitate is filtered and ground, and sieved through a 75 mesh sieve to obtain CMSS-g-MA powder.

[0074] (2) glycine betaine and water are mixed and stirred uniformly, then the CMSS-g-MA powder is added and heated to 60℃ for 1.5 hours, and the mass ratio of glycine betaine, water and CMSS-g-MA powder is 1:6:3. After completion, the reaction liquid is spray dried to obtain GB / CMSS-g-MA powder, as shown in Figure 12 .

[0075] (3) take the following proportions of components: sulphoaluminate cement 4 parts by weight, 42.5 ordinary portland cement 5 parts by weight, polycarboxylic acid water reducer 0.06 parts by weight, water-based epoxy resin emulsion with solid content of 40wt.% 0.5 parts by weight, silane coupling agent (KH-570) 0.1 parts by weight, GB / CMSS-g-MA powder of this embodiment 0.7 parts by weight, hydroxyethyl cellulose 0.025 parts by weight. Mix the above components uniformly to obtain a low-temperature fluid curing agent.

[0076] (4) take the following proportions of components: soil 70 parts by weight, low-temperature fluid curing agent of this embodiment 12 parts by weight, and mixing water 28 parts by weight. Mix the above raw materials uniformly to obtain a cured soil building material.

[0077] Performance test: the same as the above-mentioned embodiment 1, the performance index of the cured soil building material prepared in this embodiment is tested, wherein: the 12h hydration product XRD test result is as shown in Figure 13 The compressive strength test is as shown in Figure 14The results are shown in the following table. Meanwhile, from the XRD test results, it can be seen that the cured soil building material of the present embodiment has a low degree of hydration after low-temperature curing, and the hydration activity at low temperature is insufficient, and the frost resistance is reduced:

[0078] Example 6: A preparation process of a cured soil building material, comprising the following steps: (1) Mix starch with hot water at 80°C at a mass ratio of 1:5, then add alkali solution (10% mass fraction of sodium hydroxide solution) and 2-bromoacetic acid sodium, heat to 60°C and react for 1.5 hours, the mass ratio of 2-bromoacetic acid sodium, starch and alkali solution is 0.52:2.2:0.43. After completion, adjust the reaction system to neutral with dilute hydrochloric acid, then add anhydrous ethanol for precipitation, the mass ratio of the reaction system and anhydrous ethanol is 1:1.7. After completion, filter out the precipitate and grind, then pass through a 100 mesh sieve to obtain modified starch.

[0079] (2) Mix glycine betaine with water and stir evenly, then add the modified starch and heat to 60°C for 2 hours, the mass ratio of glycine betaine, water and modified starch is 1:6:2.5. After completion, the reaction liquid is spray dried to obtain GB / CMSS-g powder, as shown in Figure 15 .

[0080] (3) Take the following proportions of components: sulphoaluminate cement 3.2 parts by weight, 42.5 ordinary portland cement 4 parts by weight, polycarboxylic acid water reducer 0.05 parts by weight, water-based epoxy resin emulsion with a solid content of 40wt.% 0.45 parts by weight, silane coupling agent (KH-550) 0.08 parts by weight, GB / CMSS-g powder of the present embodiment 0.6 parts by weight, hydroxyethyl cellulose 0.02 parts by weight. Mix the above components evenly to obtain a low-temperature fluid curing agent.

[0081] (4) Take the following proportions of components: soil 73 parts by weight, low-temperature fluid curing agent of the present embodiment 14 parts by weight, mixing water 30 parts by weight. Mix the above raw materials evenly to obtain a cured soil building material.

[0082] Performance test: the same as in Example 1 above, the performance indicators of the cured soil building material prepared in the present embodiment are tested, wherein: the XRD test results of 12h hydration product are shown in Figure 16 , the compressive strength test is shown in Figure 17 , and the results are shown in the following table. Meanwhile, from the XRD test results, it can be seen that the cured soil building material of the present embodiment has a low degree of hydration after low-temperature curing, and the hydration activity at low temperature is insufficient, and the frost resistance is reduced:

[0083] Example 7: A preparation process of the cured soil building material, comprising the following steps: (1) Take the following proportions of components: 3 parts by weight of sulphoaluminate cement, 3 parts by weight of 42.5 ordinary Portland cement, 0.4 parts by weight of water-based epoxy resin emulsion with a solid content of 43 wt.%, 0.07 parts by weight of silane coupling agent (KH-560), 0.5 parts by weight of GB / CMSS-g-MA powder of the above-mentioned Example 2, and 0.01 parts by weight of hydroxyethyl cellulose. Mix the above components uniformly to obtain a low-temperature fluid curing agent.

[0084] (2) Take the following proportions of components: 78 parts by weight of soil, 15 parts by weight of the low-temperature fluid curing agent of the present example, and 32 parts by weight of mixing water. Mix the above raw materials uniformly to obtain a cured soil building material.

[0085] Performance test: The performance indicators of the cured soil building material prepared in the present example were tested in the same way as in the above-mentioned Example 1, wherein the XRD test results of the 12h hydration product are shown in Figure 18 , the compressive strength test results are shown in Figure 19 , and the results are shown in the following table. At the same time, from the XRD test results, it can be seen that the cured soil building material of the present example still maintains good hydration degree after low-temperature curing, and the hydration is more sufficient, which indicates that its anti-freezing performance is good. However, its setting rate is significantly accelerated, resulting in a significant decrease in fluidity, and thus the self-leveling ability is decreased:

[0086] The above-mentioned is only the preferred embodiment of the present application, and is not used to limit the present application, although the present application has been described in detail with reference to the foregoing embodiments, and for those skilled in the art, the technical solutions recorded in the foregoing embodiments can still be modified, or some technical features can be replaced equivalently. Any modification, equivalent replacement, improvement, etc. made within the spirit and principles of the present application shall be included in the protection scope of the present application.

Claims

1. A preparation process for a low-temperature fluidized bed curing agent, characterized in that, Includes the following steps: (1) Add starch to hot water and stir to gelatinize. Then add alkaline solution and sodium 2-bromoacetate and heat to react. After the reaction is completed, adjust the reaction system to neutral, then add ethanol to precipitate. After separating the precipitate, grind it to obtain modified starch. (2) Add the modified starch to water, stir evenly and then remove oxygen; then add maleic anhydride and persulfate and heat to react; after completion, add ethanol to precipitate, separate the precipitate and grind to obtain CMSS-g-MA powder; (3) Add glycine betaine to water and stir evenly, then add the CMSS-g-MA powder and heat to react; after completion, spray dry the resulting reaction solution to obtain modified betaine powder. (4) Using sulfoaluminate cement, ordinary silicate cement, polycarboxylate superplasticizer, waterborne epoxy resin emulsion, silane coupling agent, the modified betaine powder, and hydroxyethyl cellulose as raw materials, mix them evenly to obtain the low-temperature flow curing agent.

2. The preparation process of the low-temperature fluidized bed curing agent according to claim 1, characterized in that, In step (1), the mass ratio of starch to hot water is 1:5~5.8; Alternatively, in step (1), the temperature of the hot water is 80~85℃.

3. The preparation process of the low-temperature fluidized bed curing agent according to claim 1, characterized in that, In step (1), the mass ratio of sodium 2-bromoacetate, starch, and alkaline solution is 0.5~0.6:2~2.4:0.4~0.44; Alternatively, in step (1), the mass fraction of the alkali solution is 10-12%.

4. The preparation process of the low-temperature fluidized bed curing agent according to claim 1, characterized in that, In step (1), the heating reaction is carried out at a temperature of 60-65°C for 1-2 hours. Alternatively, in step (1), the alkaline solution includes at least one of sodium hydroxide, potassium hydroxide, ammonia, and lithium hydroxide. Alternatively, in step (1), at least one of dilute hydrochloric acid and dilute HBr is used to adjust the reaction system to neutral. Alternatively, in step (1), the mass ratio of the reaction system to ethanol is 1:1.5~2; Alternatively, in step (1), the modified starch has a fineness of 75-100 mesh.

5. The preparation process of the low-temperature fluidized bed curing agent according to claim 1, characterized in that, In step (2), the mass ratio of the modified starch to water is 1:8~9; Alternatively, in step (2), the persulfate includes at least one of ammonium persulfate and potassium persulfate.

6. The preparation process of the low-temperature fluidized bed curing agent according to claim 1, characterized in that, In step (2), the mass ratio of the modified starch, maleic anhydride, and persulfate is 10~12:1.8~2.2:0.1~0.2; Alternatively, in step (2), the heating reaction is carried out at a temperature of 60-65°C for 1-2 hours. Alternatively, in step (2), the fineness of the CMSS-g-MA powder is 75~100 mesh.

7. The preparation process of the low-temperature fluidized bed curing agent according to claim 1, characterized in that, In step (3), the mass ratio of glycine betaine, water, and CMSS-g-MA powder is 1:6:2~3; or, in step (3), the heating reaction temperature is 60~65℃ and the time is 1~2h.

8. The preparation process of the low-temperature fluidized bed curing agent according to any one of claims 1-7, characterized in that, In step (4), the proportions of each component in the raw materials are as follows: 3-4 parts by weight of sulfoaluminate cement, 3-5 parts by weight of ordinary silicate cement, 0.05-0.06 parts by weight of polycarboxylate superplasticizer, 0.4-0.5 parts by weight of waterborne epoxy resin emulsion, 0.07-0.1 parts by weight of silane coupling agent, 0.5-0.7 parts by weight of modified betaine powder, and 0.01-0.025 parts by weight of hydroxyethyl cellulose.

9. The preparation process of the low-temperature fluidized bed curing agent according to any one of claims 1-7, characterized in that, In step (4), the silane coupling agent includes at least one of KH-550, KH-560, and KH-570; or, in step (4), the solid content of the aqueous epoxy resin emulsion is 40~43 wt.%.

10. A solidified soil building material, characterized in that, It comprises the following components: 70-78 parts by weight of soil, 12-15 parts by weight of the low-temperature fluidized solidifying agent obtained by the preparation process according to any one of claims 1-9, and 22-27 parts by weight of mixing water.

Citation Information

Patent Citations

  • Early-strength water reducing agent for recycled aggregate concrete and preparation method thereof

    CN111423150A

  • Environment-friendly anti-freezing concrete and preparation method thereof

    CN113149541A

  • Dust suppressant as well as preparation method and application thereof

    CN116606631A

  • Bentonite-starch composite thixotropic agent as well as preparation method and application thereof

    CN119241125A

  • Roadbed soil cement cementing material curing agent and use method thereof

    CN120081637A

Cited By

  • Preparation process of anti-crack marine cement material based on carbide slag-based expanding agent

    CN121894993A